CYP2A6 Genetic Polymorphism and Nicotine Metabolism of Male Smokers in Indonesia - Soliha, Chaliza; Soeroso, Noni Novisari; Ananda, Fannie Rizki; Zain-Hamid, Rozaimah; Bihar, Syamsul; Lim, Darren Wan-Teck (Faculty of Medicine Universitas Airlangga, 2024)
Introduction: One of the main ingredients in cigarettes is nicotine, which has a significant impact on a person's dependence on cigarettes. Nicotine can be detected in a smoker's urine as a sign that his body is processing nicotine. The important enzyme CYP2A6 is involved in nicotine metabolism. This study aimed to determine the relationship between CYP2A6 genetic polymorphisms and nicotine metabolism among male smokers in Indonesia. Methods: This study included 100 male smokers who met the inclusion criteria in a cross-sectional design using a consecutive sampling between the ages of 20 and 65 years old. Restrictions fragment length polymorphism (RFLP) of the polymerase chain reaction (PCR) was applied to examine the genetic polymorphism of CYP2A6, and nicotine metabolite levels in urine were examined by high-performance liquid chromatography (HPLC) examination. Results: This study involved one hundred smokers, and 78 tested positive for the CYP2A6 polymorphism. The CYP2A6 genetic polymorphism and nicotine metabolism were not significantly correlated (p-value > 0.05). Allele *1A and genotype 1B/1B were more common in this study population. The majority of study participants had fast metabolic rates. Conclusion: No correlation was seen between the genetic polymorphisms of CYP2A6 and nicotine metabolism in Indonesian male smokers. Consequently, it is crucial to conduct future research in diverse populations with larger samples.